Indicadores cognitivos, linguísticos, comportamentais e acadêmicos de pré-escolares prematuros e nascidos a termo - Oliveira, Christyne Gomes Toledo de (2008)
The prematurity and low birth weight are risk factors for the development and school performance. This study evaluated the relationship between the conditions of birth and development of 34 children under 5 years old, born in public hospital, divided into 17 children with pre-term and low weight (G1-PT-BP), and 17 children born to term and weight =2.500g (G2-AT). The areas examined were : (a) cognitive – nonverbal psychometric tests (Scale of Mental Maturity Columbia and Colorful Progressive Matrices of Raven) and assisted tests (Children's Analogical Thinking Modifibility-CATM, facilitator operations and behaviors of cognitive performance protocols and affective-motivational behaviors protocol (Applications of Cognitive Functions Scale-ACFS), (b) language (Peabody Picture Vocabulary Test - PPVT and Language Development Survey de Rescola - LDS), (c) academic (Evaluation of Assessment of Basic code for Literacy-IAR), (d) behavioral (Child Behavior ChecklistCBCL). Neonatal and socio-economic data were collected . In all evidence, the G1 (PT-BP) performance was worse, except for Raven. Both groups showed no difficulties in basic skills for literacy and their cognitive performance were within the average (Columbia and Raven), but showed delay in receptive language (PPVT). There were significant differences between groups, with lower performance of G1 (PT-BP) in the academic, expressive language (LDS), behavioral and cognitive (Columbia, and less cognitive and conduct operations facilitators in CATM) areas. There were correlations between gestational age and cognitive (Columbia) and linguistic (LDS) performances , and between birth weight and cognitive operations and conduct facilitators in CATM. The data confirm the need for monitoring the development of these children, especially in cases of prematurity.